Navigating Progressivism in the Middle of the Traditional Paradigm: Women Teachers' Strategies in Creating an Inclusive Learning Environment - Poudel, Ranisha; Subedi, Ramila; Shrestha, Milan (Universitas Nurul Jadid, 2024)
This research focuses on exploring the progressive learning practices applied by female teachers who graduated from education in the Kathmandu Valley, Nepal, as well as the social and institutional barriers they face. The main objective of this study is to understand how teachers implement participatory, student-centered learning in an environment that is still dominated by traditional and score-oriented approaches. This study uses a qualitative approach with a descriptive method to describe the teachers' experiences and views related to the application of progressivism in the classroom. Data were collected through in-depth interviews and classroom observations of four female teachers in several schools that adopted progressive education principles. The data analysis technique used is the Miles and Huberman model, which involves the stages of data reduction, data presentation, and conclusion drawing to identify the main themes of learning practices and challenges faced by teachers. The results show that although teachers have a strong understanding of the principles of progressive learning, they face obstacles from schools and parents who still adhere to conventional methods. Teachers seek to overcome these barriers through individual student observation and flexible adjustments to teaching methods, such as project-based learning and creative expression, to increase student engagement. The implications of this study suggest that institutional support and collaboration with parents are essential to enable the effective implementation of progressivism. This research contributes to the progressive education literature by highlighting how social and cultural variables affect the application of educational theories in developing countries, as well as providing practical guidance for educators in facing similar challenges in different contexts.